Mekanisme Kerja Dewan Pengawas Syari'ah dan Sistem Pelaporan DPS di BPRS - Muhammad Achid Nurseha; Khoirotun Nisatasni (LABATILA : Jurnal Ilmu Ekonomi Islam, 2021)
This research examines the working mechanism of the Sharia Supervisory Board (DPS) in Islamic banking in Indonesia. This research adopts content-based analytical methods, and legal regulations, descriptive analysis studies related to the research topic. The data used is based on relevant sources and relies on several research journals that have been done previously. The method used in this research is a qualitative approach method. Qualitative research is research that is descriptive in nature and tends to use analysis. The results of the study conclude that the DSN MUI as an institution that issues fatwas can coordinate and equate perceptions with DPS placed in Islamic banks in Indonesia in supervising Islamic banking operations.